Demokrasi Dalam Pendidikan Islam - Nursyahrani Fahmin; Kasyful Anwar; Sya’roni Sya’roni; Anistianingsih Anistianingsih (BADAN PENERBIT STIEPARI PRESS, 2023)
This paper discusses democracy in Islamic education, this paper aims to know in depth about the definition of democracy, democracy in Islamic education, Problems of Islamic education democracy, Islamic education democracy solutions , Implementation of Islamic education democracy. Democracy regarding education where many problems often occur, one of which is a problem that often occurs in the world of education according to the observations of researchers, such as: schools, especially teachers, are often a reference of many things that are not desired by the community. When children are dependent on watching television, it is the school that is targeted because it is considered not to provide maximum media education. When there are frequent brawls, it is the school that is most highlighted because schools lack value education. When people are not familiar with technology, schools are also the focus because of lack of attention to the times, and there are many examples of other problems. The purpose of this study is to know the concept of democracy in Islam and to explain democratic education according to Islam. The research method used is a basic theoretical method that uses data from materials, namely library research, where the author reads and studies books or literature related to the problem under study. Democratic principles in Islamic Education are: There is freedom for educators and students, where freedom here includes: freedom to work, freedom to develop potential and freedom of opinion. Equality towards learners in Islamic education. Because, Islam provides equal opportunities for all learners to get an education or learn. Respect for individual dignity in Islamic education.